Повышение качества подготовки студентов строительного профиля по специ- альным учебным дисциплинам - Ешниязов, Р.Н (SCIENCE and SOCIETY, 2023)
The article presents the results of the author's research conducted among senior students of the Faculty of Civil Engineering of Karakalpak State University between 2020-2022. These studies were conducted according to the basic knowledge of the specialty that they studied during the first three years of their studies. The results of the study show that currently undergraduate students are not able to adequately preserve knowledge in the initial courses, and especially to use this knowledge in practical activities when designing. Based on the conducted research, the directions of future work for a significant increase are proposed in the level of training of students of the construction direction.
Keywords: higher education; assessment of students' knowledge; inert knowledge